Research on video streaming media cooperative downloading in vehicular ad hoc network - Liang CHEN; Jun WANG; Rong CHEN; Xiang GU; Jin WANG; Jie WAN (Tongxin xuebao)
The same direction multi-hop downloading network flow model was proposed for vehicle communication range and channel competition under forwarding.According to the model and video streaming media characteristic,the same ＆amp; opposite direction cooperative downloading quality of service (SODCD-QoS) scheme was presented.First,the same direction vehicles helped the target vehicle to achieve multi-hop cooperative downloading.It can reduce the waste of time which the target vehicle has to wait for opposite direction cooperative vehicle.Secondly,the next base stations loaded data into eligible opposite direction vehicles according to vehicles option strategy based on time first or picture quality first.Then the opposite direction vehicles helped the target vehicle to achieve one-hop cooperative downloading.NS simulations show that the SODCD-QoS scheme is better than DSRelay and VCoDS algorithm in terms of download time.Further,the new scheme can maintain good picture quality PSNR.